2020
DOI: 10.1507/endocrj.ej19-0324
|View full text |Cite
|
Sign up to set email alerts
|

Association of diabetic nephropathy with the severity of obstructive sleep apnea-hypopnea syndrome in patients with type 2 diabetes mellitus

Abstract: This study aimed to analyze the effect of the severity of obstructive sleep apnea-hypopnea syndrome (OSAHS) on diabetic nephropathy (DN) in patients with type 2 diabetes mellitus (T2DM). A total of 322 patients with T2DM participated in this cross-sectional study. OSAHS was diagnosed according to the apnea-hypopnea index (AHI) and it was categorized as follows: normal, mild, moderate, and severe. Relevant clinical data retrieved from medical charts were cross-analyzed between different groups. The relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…The results showed that the height of children with OSAHS was lower than that of HC group, which was consistent with the research of Johnson C ( 29 ) and may due to the decrease of growth hormone secretion caused by poor sleep quality of children with OSAHS. Similarly, the two groups had statistical differences in Scr and TC, which was consistent with the studies of other scholars ( 30 , 31 ). Secondly, we performed small RNA sequencing to detect the expression profile of tRFs in 5 pairs of OSAHS children and control specimens.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that the height of children with OSAHS was lower than that of HC group, which was consistent with the research of Johnson C ( 29 ) and may due to the decrease of growth hormone secretion caused by poor sleep quality of children with OSAHS. Similarly, the two groups had statistical differences in Scr and TC, which was consistent with the studies of other scholars ( 30 , 31 ). Secondly, we performed small RNA sequencing to detect the expression profile of tRFs in 5 pairs of OSAHS children and control specimens.…”
Section: Discussionsupporting
confidence: 91%
“…OSA is found in 30–60% of patients with heart failure, 42% of patients with ischemic stroke, 85% of patients with atrial fibrillation [ 5 ], 41.89% of patients with hypertension [ 6 ] and 57.69% of patients with hypertensive emergencies [ 7 ]. A study from China found that the prevalence of OSA in admitted Type 2 diabetes mellitus patients was 60.0% [ 8 ], while patients with Type 2 diabetes mellitus who had diabetic nephropathy had an even higher prevalence of OSA, at 88.2% [ 9 ].…”
mentioning
confidence: 99%